Privatization Effect on Shareholder Value in the Jordanian State Owned Enterprises - Darwazeh, Riyad Neman; Dabaghia, Mohammad (International Journal of Economics and Financial Issues, 2018)
Privatization is the act of reducing the role of government or increasing the role of the private institutions of society in satisfying people's needs; it means relying more on the private sector and less on government. The Jordanian government adopted a privatisation program in 1996 to enhance the efficiency and productivity of government owned companies. The principal objective of this study is to examine the effects of the privatisation program on enhancing the performance of state-owned enterprises in Jordan. Data from 23 companies covering the period from 1996 to 2013 have been used to test the research hypotheses. The data was then analysed using dependent samples t-tests and multiple regression analysis. The results analysis shows that the privatisation program had a significant positive relationship with shareholder value in the Jordanian state owned enterprises. Keywords: Privatization, State Owned Enterprises, Shareholder Value JEL Classifications: L32, L33